Aliran Salaf Khalaf: Suatu Perbandingan dari Segi Method dan Konsep-konsep Utama - Mat Leh, Hassan (Jurnal Usuluddin, 1995)
This article studies the thoughts of khalf and development of Ilm al-Kalam in the Islamic History.